Nonverbal learning disabilities in children bridging the gap between science and practice - Davis, John Martin 1949- (Springer eBooks., 2011)
Although it has yet to be recognized by the American Psychiatric Association's Diagnostic and Statistical Manual (DSM), nonverbal learning disabilities (NVLD) in children are a growing concern. NVLD are receiving increased attention from researchers as well as from clinicians encountering these conditions in their young clients. At the same time, reliable information on effective interventions for NVLD has lagged behind this interest. Nonverbal Learning Disabilities in Children: Bridging the Gap Between Science and Practice offers a well-rounded understanding of NVLD, placing it within the context of other developmental disorders, most notably high-functioning autism and Asperger's syndrome. The most current genetic, environmental, and neurobiological theories of and research into the causes of NVLD (e.g., the white matter model), in-depth diagnostic methods, and quality interventions are examined. Using an evidence-based approach, this groundbreaking volume: Conceptualizes NVLD as a disorder with subtypes. Differentiates between diagnostic criteria for NVLD and Asperger's Syndrome. Analyzes the co-occurrence of NVLD with other developmental disabilities and psychological disorders. Provides a comprehensive psychoeducational assessment model. Describes efficacious treatments and supports their empirical validation. Offers guidelines for sustaining treatment gains through effective collaboration of school personnel and family members. Nonverbal Learning Disabilities in Children is a must-have reference for researchers, practitioners, and graduate students in school and clinical child psychology, education, speech-language therapy, and other disciplines and professions involved in identifying and treating children with NVLD.